Combination Treatment of Cervical Cancer Using Folate-Decorated, pH-Sensitive, Carboplatin and Paclitaxel Co-Loaded Lipid-Polymer Hybrid Nanoparticles - Wang J (Dove Medical Press, 2020)
Junjian Wang 1–3 1Institution of Cancer and Basic Medicine, Chinese Academy of Sciences, Hangzhou 310022, Zhejiang Province, People’s Republic of China; 2Department of Gynecological Surgery, Cancer Hospital of the University of Chinese Academy of Sciences, Hangzhou 310022, Zhejiang Province, People’s Republic of China; 3Department of Gynecological Surgery, Zhejiang Cancer Hospital, Hangzhou 310022, Zhejiang Province, People’s Republic of ChinaCorrespondence: Junjian WangInstitution of Cancer and Basic Medicine, Chinese Academy of Sciences, No. 1 East Banshan Road, Gongshu District, Hangzhou City, Zhejiang Province, People’s Republic of ChinaEmail wangjunjian@protonmail.comPurpose: Cervical cancer is one of the most common causes of death among women globally. Combinations of cisplatin, paclitaxel, bevacizumab, carboplatin, topotecan, and gemcitabine are recommended as first-line therapies.Methods: This study focuses on the development of folate-decorated, pH-sensitive lipid-polymer hybrid nanoparticles (LPNs). Loading carboplatin (CBP) and paclitaxel (PTX), LPNs were expected to combine the therapeutic effects of CBP and PTX, thus show synergistic ability on cervical cancer.Results: FA-CBP/PTX-LPNs showed the sizes of 169.9 ± 5.6 nm, with a narrow size distribution of 0.151 ± 0.023. FA-CBP/PTX-LPNs exhibited pH-responsive drug release, high cellular uptake efficiency (66.7 ± 3.1%), and prominent cell inhibition capacity (23 ± 1.1%). In vivo tumor distribution and tumor inhibition efficiency of FA-CBP/PTX-LPNs was the highest, with no obvious body weight lost.Conclusion: High tumor distribution and remarkable antitumor efficiency obtained using in vitro as well as in vivo models further proved the FA-CBP/PTX-LPNs is a promising tool for cervical cancer therapy.Keywords: cervical cancer, folate, pH-sensitive, carboplatin, paclitaxel, lipid-polymer hybrid nanoparticles